Factors associated with survival of veterans with gastrointestinal neuroendocrine tumors - Balmadrid, Bryan L.; Thomas, Catherine M.; Coffman, Cynthia J.; Liddle, Rodger A.; Fisher, Deborah A. (My University, 2012)
Background. Gastrointestinal (GI) neuroendocrine tumor (NET) incidence has been increasing; however, GI NET within the national Veterans Affairs (VA) health system has not been described. Methods. We used the VA Central Cancer Registry to identify the cohort of patients diagnosed with GI NET in 1995–2009. Cox regression models were constructed to explore factors associated with survival. Results. We included 1793 patients with NET of the stomach (9%), duodenum (10%), small intestine (24%), colon (19%) or rectum (38%). Twenty percent were diagnosed in 1995–1999, 35% in 2000–2004, and 45% in 2005–2009. Unadjusted 5-year survival rates were: stomach 56%, duodenum 66%, small intestine 52%, colon 67%, and rectum 84%. Factors associated with shorter survival were increasing age, hazard ratio (HR) 1.05 (95% CI 1.04–1.06), NET location [compared to rectum: stomach HR 2.26 (95% CI 1.68–3.05), duodenum HR 1.70 (95% CI 1.26–2.28), small intestine HR 1.85 (95% CI 1.42–2.42), and colon 1.83 (95% CI 1.41–2.39)], stage [compared to in situ/local: regional HR 1.15 (95% CI 0.90–1.47), distant HR 2.38 (95% CI 1.87–3.05)], and earlier period of diagnosis [compared to 1995–1999: 2000–2004 HR 0.70 (95% CI 0.59–0.85), 2005–2009 HR 0.43 (95% CI 0.34–0.54)]. Conclusions. The incidence of GI NET has also increased over time in the VA system with similar survival rates to those observed in non-VA settings. Worsened survival was associated with older age, tumor site, advanced stage, and earlier year of diagnosis.